Ancient Vilnius - 700: history of book publishing, book rarities, historical libraries - Bondar Nataliia; Rudakova Yulia; Tsiborovska-Rymarovych Iryna (Bìblìotečnij vìsnik, 2023)

(untitled)
The purpose of the study is to present old printed editions from the fund of the V. I. Vernadskyi National Library of Ukraine, related to the publishing activities of Vilnius printers, historical book collections, political and cultural figures that link Ukrainians to the Lithuanian capital. The publication is timed to the 700th anniversary of the capital of Lithuania, Vilnius, which coincides with its first mention in documentary sources and was widely celebrated by the world community. The research methodology is based on the application of general scientific and specialized research methods (principles of historicism, systematicity and objectivity; bibliological, bibliographic, paleographic and source studies methods). Scientific novelty. For the first time, old printed sources related to Vilnius, which are stored in the V. I. Vernadskyi National Library of Ukraine fund, have been compiled and analyzed. Consideration was given to rare editions from the collection of the V. I. Vernadskyi National Library of Ukraine, printed in Vilnius during the 16th-19th centuries. Among them are the Cyrillic editions of the printing houses of Mamonichi and the Vilna Holy Spirit Brotherhood. As well as the printing houses of the Vilna Jesuit Academy, Basilian, Franciscan, and Piar monasteries, which published works in Latin script in Polish and Latin languages. Mention is made of Ukrainian engravers, writers, theologians, state and church figures, and representatives of the social elite whose lives and activities had direct ties to Vilnius. The historical and librarian characteristics of institutional and private collections whose funds contained Vilnius prints, the fates of which connect Ukraine and Lithuania, are presented. Conclusions. This material demonstrates the close relationships between the Ukrainian and Lithuanian book cultures. The given facts illustrate the existence of Vilnius publications, printed in Cyrillic and Latin fonts, on Ukrainian territory. The described copies testify to the different informational content of old printed editions from the V. I. Vernadskyi National Library of Ukraine fund, related to the ancient capital of the Grand Duchy of Lithuania, through visual presentation, funds of monastic and magnate book collections, the fate of which is connected with Vilnius and Kyiv. The presented factual material can be used in bibliographic and cultural publications.